Understanding Structural, Governance and Regulatory Incentives for Improved Utility Performance: A Comparative Analysis of Electricity Utilities in Tanzania, Kenya and Uganda - Twesigye, Peter Rwakifaari (Graduate School of Business (GSB), 2022)
Electricity utilities in most African countries have failed to deliver adequate, reliable and competitively priced electricity to support economic growth and improve the welfare of their populations. Despite more than two decades of power sector reforms, outcomes have been varied and often disappointing with many utilities still experiencing challenges in service delivery, operational efficiency and financial sustainability. Power sector and regulatory reforms involve changes to structural, regulatory and governance frameworks and incentives that potentially impact utility performance in Africa. This thesis draws on the literature of power sector reforms and applies a Principal–Agent theory lens to obtain a deeper understanding of the dynamics between principals (government/regulators/capital providers) and agents (utility managers) and how these impact on performance. A comparative case study analysis was undertaken of power utilities in three East Africa countries that have experienced different levels of reform: TANESCO in Tanzania, KPLC in Kenya and Umeme in Uganda. TANESCO remains a vertically integrated, state-owned utility and has performed the worst. KPLC is an unbundled, mixed capital utility, with a partial listing on the Nairobi Stock Exchange, but still majority government owned, and has performed better. Umeme is fully unbundled, operates as a private concession, is also listed on the stock exchange, and is the most financially sustainable of the three utilities. However, this ranking between the three utilities is not consistent across all performance measures, and an analysis of structural, governance and regulatory incentives, principal–agent dynamics – examining issues such as information asymmetry, moral hazard, adverse selection, amongst others – provides deeper insights into how reforms have impacted technical and economic performance. Findings also show that: (i) the deeper and more extensive the power sector reforms, the more incentives there are for improved performance; (ii) while the existence of an independent regulator is important, capability issues are also critical; (iii) private concessions provide deeper incentives for improved performance; (iv) strong management incentives are critical for the success of any utility; and (v) private capital, either through equity or debt financing, imposes additional compliance obligations and incentives for improved utility performance.